2019
DOI: 10.3390/cancers11020135
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of KV11.1 Potassium Channel Modulates F-Actin Organization During Cell Migration of Pancreatic Ductal Adenocarcinoma Cells

Abstract: Cell migration exerts a pivotal role in tumor progression, underlying cell invasion and metastatic spread. The cell migratory program requires f-actin re-organization, generally coordinated with the assembly of focal adhesions. Ion channels are emerging actors in regulating cell migration, through different mechanisms. We studied the role of the voltage dependent potassium channel KV 11.1 on cell migration of pancreatic ductal adenocarcinoma (PDAC) cells, focusing on its effects on f-actin organization and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
(68 reference statements)
4
18
0
Order By: Relevance
“…At points of ECM-cell contact, specialized structures are formed, which are termed focal adhesions. Some components of focal adhesions contribute to cell migration in PDAC and participate in structural links between the actin cytoskeleton and membrane receptors, whereas others are signaling molecules (Manoli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At points of ECM-cell contact, specialized structures are formed, which are termed focal adhesions. Some components of focal adhesions contribute to cell migration in PDAC and participate in structural links between the actin cytoskeleton and membrane receptors, whereas others are signaling molecules (Manoli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Kv11.1 could function as an oncogene in PDAC and be a potential target of miR-96 (Feng et al, 2014). Further investigations showed that Kv11.1 promotes pancreatic cancer cell migration, by modulation of F-actin organization and dynamics (Lastraioli et al, 2015b) suggesting its involvement in cancer metastasis (Arcangeli et al, 2014;Manoli et al, 2019).…”
Section: Kv Channelsmentioning
confidence: 97%
“…hERG1 was shown to modulate β1-integrin mediated VEGF-A secretion through the recruitment of PI3K and AKT[72]. In PC hERG1 over-expression was reported in 59% of tumors[66] where it promoted cancer cell migration via modulation of F-actin organization[64]. hERG1 expression was also associated with lymph node involvement, tumor grade, TNM stage and poor patient prognosis[66].…”
Section: Potassium Channelsmentioning
confidence: 99%